The role of Job description and Perceived organizational support to achieving An Excellent Job performance - An Exploratory study of the views of a sample of department heads at Sulaimaniyah University. - محمد, برشنك صالح; سعيد, سولاف عزالدين (Journal of Economics and Administrative Sciences, 2017)
This research Sought to identify the correlation relationships and the impact of each of the job description and perceived organizational support, Excellent Job performance of the heads of academic departments in the faculties of the University of Sulaymaniyah Iraqi Kurdistan Region, totaling (89) as President, and to achieve this was Default plan includes research variables as well as the formulation of a number of preparation fundamental assumptions, and researchers used a questionnaire for this purpose as a tool head of the collection of data and information, as it was distributed (80) copies, and the number of retrieved them (76) a copy of a valid statistical analysis, as well as conducting personal interviews with (11) heads of departments in All S university surveyed, with the use of a number of statistical methods to test hypotheses.             Because of the limited studies on the relationship and influence between these variables in the general Iraqi environment and specially in Kurdish environment within the limits of informed researchers, therefore present their research to address these variables within a holistic framework, and generally tried to research the answer to the following question: What is the nature of the correlation and influence relationships for each of the Job description and perceived organizational support both individually as well as two societies together in achieving Excellent Job performance in the surveyed university? The research has come to a set of conclusions including: a weakness by the university regarding the status of the right staff in the right job, it turns out that there are shortcomings to some extent by the university with regard to overall organizational support through its determinants, and therefore a reflection on the performance of its employees, which limits improve their performance level of Excellent performance, also shows a correlation and impact of relationships significant statistical evidence of both job descriptions and Excellent Job performance, as well as perceived organizational support and Excellent Job performance, and finally job description and perceived organizational support together with the Wireless Excellent Job performance in the university surveyed, and depending on that the researchers have presented a set of recommendations and proposals consistent with those conclusions.